1979
DOI: 10.1042/bj1770531
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of subcomponent C1q of the first component of bovine complement

Abstract: Bovine Clq, a subcomponent of the first component of complement, was purified in high yield by a combination of euglobulin precipitation, and ion-exchange and molecularsieve chromatography on CM-cellulose and Ultrogel AcA 34. Approx. 12-16mg can be isolated from 1 litre of serum, representing a yield of 13-18%. The molecular weight of undissociated subcomponent Clq, as determined by equilibrium sedimentation, is 430000. On sodium dodecyl sulphate/polyacrylamide gels under non-reducing conditions, subcomponent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The overall amino acid composition of mouse C lq is very similar to that of human C lq (Table 2) and those reported for the rabbit (Reid et al, 1972) and bovine Clq (Campbell et al, 1979). Notable features of the amino acid composition are the high glycine content and the presence of hydroxyproline and hydroxylysine, suggestive of a collagen-like sequence in mouse C lq also.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The overall amino acid composition of mouse C lq is very similar to that of human C lq (Table 2) and those reported for the rabbit (Reid et al, 1972) and bovine Clq (Campbell et al, 1979). Notable features of the amino acid composition are the high glycine content and the presence of hydroxyproline and hydroxylysine, suggestive of a collagen-like sequence in mouse C lq also.…”
Section: Discussionsupporting
confidence: 76%
“…It is well known that collagen molecules are widely distributed among the members of the Animal Kingdom, including invertebrates, and that the complement system is probably present in invertebrates and has been conserved throughout evolution (Gigli & Austen, 1971). Not surprisingly, therefore, interest in the biochemistry or structure on C lq of various animals besides man has increased greatly, and purification and partial characterization of rabbit (Reid et al, 1972;Volanakis & Stroud, 1972;Lowe & Reid, 1974), bovine (Campbell et al, 1979), equine (McDonald & Burger, 1979), rat (Hiffken et al, 1978) and frog Clq (Alexander & Steiner, 1980) have been reported. Each has been shown to have an unusual amino acid composition (hydroxyproline, hydroxylysine and a high percentage of glycine) and to be composed of essentially the similar subunit structure.…”
mentioning
confidence: 99%
“…Immunological methods. Immunodiffusion analysis was carried out by the method of Ouchterlony (1958), as described by Campbell et al, (1979). Rocket immunoelectrophoresis was carried out by a modification to the method of Laurell (1966) described by Weeke (1973).…”
Section: Methodsmentioning
confidence: 99%
“…The precipitate was then dissolved with 32 ml of buffer B, centrifuged at 5000 g for 5 min and the supernatant dialysed against 4 litres of buffer C for 4 h. The resultant precipitate was sedimented and washed with buffer C and then dissolved with 32 ml of buffer D and centrifuged at 5000 g for 5 min. The supernatant was dialysed against 4 litres of buffer E for 5 h, and the resultant precipitate sedimented and washed with buffer E. Finally the precipitate was dissolved in 10ml of buffer F. The absorbance at 280 nm was measured and the preparation stored at -18 "C in small amounts 0.5-1 ml (c. 200 pg assuming = 0.72; Campbell, Booth & Fothergill, 1979).…”
Section: L Q Preparntiorimentioning
confidence: 99%